SAT0231 Diffusion tensor imaging and cogntive performance in NPSLE. (23rd January 2014) - Davies, K.A.; Haynes, B.; Trimble, R.; Rusted, J.; Dowell, N.
Abstract : Background: One of the most common manifestations of Neuropsychiatric SLE (NPSLE) is cognitive dysfunction, which is present in up to 80% of patients [1]. NPSLE presents a diagnostic challenge as it is not clear to what extent subtle psychiatric manifestations, such as cognitive dysfunction are a direct consequence of SLE disease activity on the brain or are a secondary to chronic illness or emotional disturbance Objectives: To investigate cognitive performance in NPSLE compared to non-NPSLE and the correlates of performance including MRI and depression and anxiety Methods: 15 NPSLE (av age=47±10y) patients were compared to 22 non-NPSLE (43±13y) and 28 healthy controls (44±12y). Measures of depression and anxiety were taken and participants completed a broad cognitive test battery. Based on a factor analysis the battery was divided into 4 domains; memory, Processing speed (SOP), executive control and compound reaction time (CRT). Diffusion tensor imaging (DTI) was used to assess white matter integrity. From this the extent (apparent diffusion coefficient) and directionality (fractional anisotropy) of diffusion were assessed. Results: Both SLE groups had significantly higher scores on depression and anxiety and lower quality of life compared to healthy controls. On cognitive tasks the NPSLE group scored significantly worse than controls on all domains, and worse than the non-NPSLE group on memory and SOP. There were no differences between the non-NPSLE patients and controls. On DTI measures the NPSLE group showed increased white matter ADC and a decrease in FA, changes which are consistent with parenchymal brain damage in this group. In the NPSLE group cognitive function correlated with both white matter FA and anxiety. Worse performance was associated with lower FA and higher anxiety. In the non-NPSLE group, processing speed (SOP and CRT) was related to depression, but no other relationships were evident. The role of anti-phospholipid antibodies, anti-Ro antibodies, corticosteroid dose and confounds such as renal involvement in SLE, hypertension and motor speed differences were considered. None of these factors explained cognitive dysfunction in the patient groups Conclusions: It seems unlikely that cognitive dysfunction in the NPSLE group can be explained by emotional disturbance, as the non-NPSLE group also showed higher depression and anxiety than controls but did not perform worse on cognitive tasks. Instead these results suggest cognitive performance in the NPSLE group was driven by changes in brain parenchyma, as they showed elevated white matter ADC relative to controls and a relationship between FA and task performance. Increased ADC and reduced FA are markers of white matter integrity [2]. This study indicates that cognitive dysfunction in many patients with NPSLE may be secondary to immune-mediated brain injury, and that Diffusion Tensor MR Imaging is a potentially useful tool in the diagnosis and management of NPSLE. References: Ainiala, H., et al., The prevalence of neuropsychiatric syndromes in systemic lupus erythematosus. Neurology, 2001. 57(3): p. 496-500. Tofts, P.S., ed. Quantitative MRI of the Brain, Measuring changes caused by disease. 2003, John Wiley and Sons Chichester. Disclosure of Interest: None Declared